Menumbuhkan Minat Berwirausaha Menjadi Pengecer Dengan Menggunakan Penentuan Harga Jual Yang Tepat - Octafiani, Aisah; Janah, Miftahul; Romahdoni, Muhamad Arief; Qotrunnada, Sabillah; Pratiwi, Zany (Prosiding Dedikasi: Pengabdian Mahasiswa Kepada Masyarakat, 2021)
Entrepreneurship is someone who creates a business, dealing with risk and uncertainty, aims to gain profit and experience growth by identifying opportunities and utilizing the necessary resources. In the modern era, entrepreneurship can be done through online media, one of which is becoming a reseller. The problem faced by the community and students is the lack of capital in starting and building a business. Reseller online business has been carried out by many people from various walks of life, including students and students. Reseller online business requires money but the capital issued is not too large. A reseller must also be able to determine the selling price precisely in order to obtain normal profits. The selling price can be determined by adding up the purchase price, operating costs and the profit margin you want to get. This study aims to foster interest and invite the public and students to start a business by selling online by becoming a reseller. Our service method in delivering material to the public and students is packaged in the form of online mini seminars. The results of the socialization and training activities conducted show that the public and students are starting to be open about online reseller business and know how to calculate the correct selling price for the online reseller business. Reseller online business in determining the selling price, don't mark up the selling price carelessly because it will affect the continuity of product sales Keywords: Selling price; Reseller; Entrepreneur